CATALOGUE OF THE STAPHYLINIDAE OF CYPRUS AND ASIA MINOR (Coleoptera) (*) - Bordoni, Arnaldo (Fragmenta entomologica, 2010)
(*) 191° contribution to the knowledge of the Staphylinidae. The catalogue includes all the species described and/or referred to Cyprus and Asia Minor until 2007 inclusive. The bibliography on the species description to that of 2001-2002 and the geonemical citations is generally available in Herman (2001) and Smetana (2002); that of the species described or mentioned in contributions appeared after 2002 can be found in the bibliography at the hend of this catalogue. Described species of Cyprus and/or Asia minor are accompanied by the following informations: type locality or list of the localitys mentioned in the description, institutions or collections where is preserved the type, whether is male or female or if you do not know the sex; if it has been designed the lectotype and the author of the designation, the distribution. Some synonymies are proposed which will be discussed elsewhere, and some general remarks on the genus Geostiba Thomson.